International Cyber Governance: Strategies And Practices Against Cybercrime - Yongsheng, Guan; Isnaini, Isnaini; Frensh, Wenggedes (Universitas Medan Area, 2024)
This research examines the complexities of cybercrime and the global efforts required to combat it. Highlighting the increasing sophistication of cyber threats, the study emphasizes the critical importance of international cooperation in cyber governance, the necessity of evolving technological solutions, policy frameworks, and effective legal measures. Utilizing a comprehensive literature review, the research defines the scope, selects relevant databases, incorporates reputable reports, evaluates sources for credibility, and meticulously documents findings. This structured approach ensures a thorough understanding of cybercrime complexities and governance measures. Key areas include balancing security and privacy, public-private partnerships, and ongoing vigilance and collaboration to strengthen cyber governance against dynamic threats.